2014
DOI: 10.12968/ijpn.2014.20.10.509
|View full text |Cite
|
Sign up to set email alerts
|

Death and caring for dying patients: exploring first-year nursing students' descriptive experiences

Abstract: Aim: To describe first-year nursing students' experiences of witnessing death and providing end-of-life care. Methods: This study is part of a larger longitudinal project. Interviews (n=17) were conducted with nursing students at the end of their first year of education. To analyse the interviews (lived-experience descriptions), a thematic analysis, 'a search for meaning' (Van Manen, 1997) was applied. Results:The results are presented within the framework of four separate themes: (1) The thought of death is m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
71
0
5

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 81 publications
(81 citation statements)
references
References 20 publications
5
71
0
5
Order By: Relevance
“…Głowacka, analyzing the death of patients as a burden factor in the professional work of nursing staff, showed that sadness (82.7%) and compassion (74%) were most often felt. Ek's research on nursing students showed that the most common emotions at the death of patients were sadness, vulnerability and helplessness associated with little experience in the profession [8][9][10][11][12].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Głowacka, analyzing the death of patients as a burden factor in the professional work of nursing staff, showed that sadness (82.7%) and compassion (74%) were most often felt. Ek's research on nursing students showed that the most common emotions at the death of patients were sadness, vulnerability and helplessness associated with little experience in the profession [8][9][10][11][12].…”
Section: Discussionmentioning
confidence: 99%
“…Nastawienie emocjonalne w zależności od stażu pracy The attitude of nursing staff towards the death and dying of the patient Postawy personelu pielęgniarskiego wobec śmierci i umierania pacjenta w pracy zawodowej personelu pielęgniarskiego pokazała, iż najczęściej w przypadku śmierci pacjenta odczuwany jest smutek (82,7%) i współczucie (74%). Badanie Ek zrealizowane wśród studentów pielęgniarstwa wykazało, iż najczęstszymi pojawiającymi się emocjami przy śmierci chorych był smutek, bezbronność i bezradność związana z małym doświadczeniem w zawodzie [8,9,10,11,12]. Badanie własne wskazało, iż w dużej mierze natężenie powstałych emocji uzależnione jest od sytuacji i okoliczności zgonu.…”
Section: Postawy Personelu Pielęgniarskiego Wobec śMierci I Umieraniaunclassified
“…Dying and death are predictable and natural phenomena of life, and their monitoring, is an integral component of nursing as a profession. In most of the places of assistance to health, nurses will find patients in care at the end of life and therefore need to be prepared for this not so easy task, but necessary in the perspective of care for the control of symptoms and the promotion of quality of life for patients and their family members (8) .…”
Section: Discussionmentioning
confidence: 99%
“…And when it comes to academic education, researches have shown that nursing students have demonstrated the need to receive continued support and have opportunities for reflection and discussion about their experiences during the practical activities and training courses on how to take care of patients in the process of terminal illness and how to face their fears and doubts before death (8) .…”
Section: Introductionmentioning
confidence: 99%
“…3 Por outro lado, estudantes de Enfermagem do primeiro ano de formação informam que pensar sobre a morte é mais assustador do que a experiência real de lidar com ela. 9 Tais resultados mostram o quanto a experiência de lidar com a morte pode ser diversa, na dependência do preparo e da disposição de cada ser humano.…”
unclassified